Gold and the global financial cycle - Afees A. Salisu; Rangan Gupta; Siphesihle Ntyikwe; Riza Demirer (Quantitative Finance and Economics, 2023)
We examine the potential of gold and other precious metals as safe havens during negative market shocks caused by the Global Financial Cycle (GFCy). We analyze a vast global vector autoregressive (GVAR) model that includes developing and emerging market countries for a total of 33 countries, from 1979:Q2 to 2019:Q4. This approach allows us to account for individual country peculiarities while also considering the transmission of global shocks. We found that during financial market distress caused by a negative GFCy shock, gold, silver and platinum all serve as hedges. Interestingly, our results suggest that silver and platinum are better hedges than gold, offering greater positive returns in response to negative GFCy shocks, especially in recent years. Overall, our findings support the benefits of investing in precious metals, as they can help investors mitigate losses resulting from global financial shocks. While the metals vary in their hedging ability, platinum and silver offer even greater protection than gold.